2018
DOI: 10.3390/molecules23040781
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Overexpression of a Novel R2R3-MYB, NtMYB2 from Chinese Narcissus Represses Anthocyanin Biosynthesis in Tobacco

Abstract: R2R3 MYB transcription factors play key functions in the regulation of secondary metabolites. In the present study, a R2R3 MYB transcriptional factor NtMYB2 was identified from Chinese narcissus (Narcissus tazetta L. var. Chinensis Roem) and functionally characterized. NtMYB2 belongs to subgroup 4 of the R2R3 MYB transcription factor family that are related to repressor MYBs involved in the regulation of anthocyanin and flavonoids. Transient expression confirmed that NtMYB2 strongly reduced the red pigmentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 59 publications
2
41
0
Order By: Relevance
“…Moreover, overexpression of MYB transcription factor, EsMybA1, from Herba epimedii (Epimedium sagittatum) was sufficient to induce high levels of anthocyanins in the transgenic tobacco and Arabidopsis, via up-regulation of major flavonoid biosynthetic pathway genes [28]. These reports indicate that some MYB transcription factors physically associate with the co-regulators such as bHLH, while other MYB transcriptional factors appear to be sufficient to induce the accumulation of anthocyanins in diverse plant species [29].…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, overexpression of MYB transcription factor, EsMybA1, from Herba epimedii (Epimedium sagittatum) was sufficient to induce high levels of anthocyanins in the transgenic tobacco and Arabidopsis, via up-regulation of major flavonoid biosynthetic pathway genes [28]. These reports indicate that some MYB transcription factors physically associate with the co-regulators such as bHLH, while other MYB transcriptional factors appear to be sufficient to induce the accumulation of anthocyanins in diverse plant species [29].…”
Section: Discussionmentioning
confidence: 90%
“…The anthocyanin biosynthesis pathway (ABP) is highly conserved and has been well studied in plants 6 . As crucial ABP regulators, the R2R3-MYB transcription factors can regulate the expression of structural genes to influence flower colour formation [8][9][10][11][12][13] . In Orchidaceae, some R2R3-MYBs have been verified to activate ABP structural genes to promote anthocyanin accumulation in Phalaenopsis 5 , Oncidium 14 and Dendrobium 15 flowers.…”
mentioning
confidence: 99%
“…It should be noted that the systems of stable transformation of many plants are difficult to develop, and strategies based on ectopic expression, though applicable, are expensive and time-consuming even in model A. thaliana plants. On the other hand, highly efficient systems of transient expression have been developed for a number of Nicotiana species, including N. benthamiana and N. excelsior (Gerasymenko et al 2019), and the functions of many plant proteins have been identified and clarified using the data on transient expression of target genes in these plants (Anwar et al 2018, Ji et al 2018Sheludko et al 2018, Thodberg et al 2018, Li et al 2019.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that gene engineering approaches, which usually entail obtaining transgenic plants, are expensive and time-consuming. In this connection, researchers studying the functional activity, substrate specificity, and physiological role of the protein products of target genes switch from obtaining stable plant transformants to using systems of transient expression of heterologous genes in model plants, such as N. benthamiana and N. excelsior (Anwar et al 2018, Ji et al 2018, Sheludko et al 2018, Thodberg et al 2018, Gerasymenko et al 2019, Li et al 2019.…”
Section: Introductionmentioning
confidence: 99%